2013
DOI: 10.1155/2013/968041
|View full text |Cite
|
Sign up to set email alerts
|

CUZD1 and Anti-CUZD1 Antibodies as Markers of Cancer and Inflammatory Bowel Diseases

Abstract: CUZD1, the CUB, and zona pellucida-like domains-containing protein 1, is a newly identified antigen of pancreatic autoantibodies (PAB) giving a reticulogranular pattern in patients with inflammatory bowel diseases, and in particular Crohn's disease. The exact mechanisms by which this pancreatic antigen becomes the target of IBD-specific pancreatic autoantibodies are unclear. At the same time, evolving data strongly support a role for CUZD1 in carcinogenesis. Human CUZD1 is mapped at chromosome 10q26.13 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…CUZD1 (CUB and zona pellucida-like domain-containing protein 1) was induced in the cecal tissue of chickens inoculated with microbiota of 4- but not 40-week-old donor hens. There is little functional information with CUZD1 except for the fact that anti-CUZD1 antibodies are used as a marker of inflammatory bowel disease in humans [ 24 ]. ISG12-2 was induced by microbiota inoculation and was also expressed at lower levels in germ-free compared with conventional chickens.…”
Section: Discussionmentioning
confidence: 99%
“…CUZD1 (CUB and zona pellucida-like domain-containing protein 1) was induced in the cecal tissue of chickens inoculated with microbiota of 4- but not 40-week-old donor hens. There is little functional information with CUZD1 except for the fact that anti-CUZD1 antibodies are used as a marker of inflammatory bowel disease in humans [ 24 ]. ISG12-2 was induced by microbiota inoculation and was also expressed at lower levels in germ-free compared with conventional chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated transcription of GP2 mRNA and translation of GP2 being a 78 kDa GPIanchored molecule with N-linked carbohydrates in intestinal biopsy samples was only shown for patients with CD in contrast to patients with UC [58]. Unlike for GP2, evidence for the expression of the other PAb target CUZD1 in the intestine and a possible immunomodulating role thereof is still lacking [106].…”
Section: Gp2 As An Autoantigenic Target In Psc-indication Of Microbiamentioning
confidence: 99%
“…Notably, these authors identified CUB/ zona pellucida-like domain-containing protein (CUZD1) as an autoantigenic target of type 2 PAB [41,45]. In this context, it is interesting to note, that almost all type 2 PAB positive sera also show a weak type 1 PAB staining by IIF at least on human pancreas [43].…”
Section: Identification Of Crd-specific Pancreatic Autoantigensmentioning
confidence: 99%